Przesłanki, negocjacje i ogłoszenie brytyjsko-tureckiej deklaracji o wzajemnej pomocy z 12 maja 1939 r. - Zdulski, Krzysztof (Acta Universitatis Lodziensis. Folia Historica, 2012)
German occupation of the Bohemia and Moravia on 15 March 1939 and the simultaneous apparent threat to Rumania began the switch in British policy of appeasement to one of containment of the III Reich. However, it did not affect relations between Turkey and the Great Britain. The prime minister Arthur Neville Chamberlain did not want to include Ankara in plans of establishing a “peaceful front” against probable German aggression in Europe in order not to antagonize Italy, which played a crucial role in British efforts to maintain security in the Mediterranean area. Only after Italian aggression on Albania (April 7th 1939), when it became clear that understanding with Benito Mussolini is unfeasible, did British government take a firmer stand towards Rome. It was decided that Greece, which was thought to be the most threaten of Italian aggression, would be given guarantees in case of hostile attack. Firmer attitude was possible also due to the fact, that Mediterranean strategy of the Great Britain had became more aggressive, which resulted as much as from change in personnel at the Admiralty House in October 1938 as from sheer incapacity to send the fleet to the Far East should war with Japan occur concurrently with war in Europe. In these circumstances British Government decided to deepen rapprochement with Ankara. Turkey was seen as a vital ally in case of war with Italy. From a military perspective Turkish army could have attacked Dodecanese Islands. What was more important Turkey could close Dardanelles to Italian shipping, which could have been a severe blow for economy of Italy (10 per cent of Italian trade and 23 per cent of Italian oil passed through this strait). From political point of view the Foreign Office recognised Turkey as a “Small Great Power”. It was thought that Ankara could have benevolently influenced the Balkan countries and as a Moslem country, bolstered Britain’s influence in its numerous Muslim colonies. Initially the British tried to persuade Turks to join them in announcing guarantees to Greece. However when Ankara refuse to do so, explaining that it cannot extend her obligations at least, when better dispositions existed for their own security, British Government decided to limit its efforts to signing the treaty of mutual assistance. On April 15th 1939 Turkey accepted British offer, which initiated a long-lasting negotiations. They were not only limited to the issue of mutual obligations, but also include such problems as: security in Balkan area and relations with France and the Soviet Union. The first phase of negotiations ended on May 12th 1939, when the British-Turkish Declaration of Mutual Aid was announced. It was a first, but simultaneously a crucial step to British-French-Turkish Treaty of Mutual Assistance, which was signed on October 17th 1939.